2012
DOI: 10.3390/md10010131
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Metabolites from an Algicolous Aspergillus versicolor Strain

Abstract: Two new compounds, asperversin A (1) and 9ξ-O-2(2,3-dimethylbut-3-enyl)brevianamide Q (2), and nine known compounds, brevianamide K (3), brevianamide M (4), aversin (5), 6,8-di-O-methylnidurufin (6), 6,8-di-O-methylaverufin (7), 6-O-methylaverufin (8), 5α,8α-epidioxyergosta-6,22-dien-3β-ol (9), ergosta-7,22-diene-3β,5α,6β-triol (10), and 6β-methoxyergosta-7,22-diene-3β,5α-diol (11), were obtained from the culture of Aspergillus versicolor, an endophytic fungus isolated from the marine brown alga Sargassum thun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 88 publications
(52 citation statements)
references
References 10 publications
1
46
1
2
Order By: Relevance
“…The dye color produced by the fungi was 187 A greyed-purple (Figure 1). Several studies of dyes produced by fungi reported that Aspergillus niger produced brown dyes [13]; yellow dyes were produced by A. terreus [14], A. calidoustus 4BV13 [15], A. versicolor [16] and Aspergillus sp. [17]; Aspergillus sp.…”
Section: Resultsmentioning
confidence: 99%
“…The dye color produced by the fungi was 187 A greyed-purple (Figure 1). Several studies of dyes produced by fungi reported that Aspergillus niger produced brown dyes [13]; yellow dyes were produced by A. terreus [14], A. calidoustus 4BV13 [15], A. versicolor [16] and Aspergillus sp. [17]; Aspergillus sp.…”
Section: Resultsmentioning
confidence: 99%
“…F18 (isolated from M. guianensis) and Penicillium sp. F3 (from E. precatoria) were cytotoxic in the tests performed against A. salina, and lead to the death of all nauplii within 24 h. Miao et al (2012) found that the substance 6.8-di-O-methylaverufin, produced by an endophytic fungus, showed significant toxicity for A. salina, with CL 50 from 0.5 μg/mL. The lethality of simple organisms such as A. salina has been used for rapid and relatively simple monitoring of biological response (Meyer et al, 1982).…”
Section: Biological Activitiesmentioning
confidence: 96%
“…Chemical investigation of various algal endophytes yielded a handful of metabolites inhibiting S. aureus as well as E. coli; namely, phenalenone derivatives and scleroderolide [69]; dicerandrol C [48]; brevianamide M, 6,8-di-Omethylaverufin, and 6-O-methylaverufin [70]; isocyathisterol [71]; Z-roquefortine C, viridicatol, penitrem A, and penijanthine A [72]. Manjusha et al [73] testified that the crude extract of endophytic fungus Streptomyces sp.…”
Section: Antibacterial Compoundsmentioning
confidence: 99%